Contracts (Rights Of Third Parties) Act 1999: Legislative Reform Of The Doctrine Of Privity In The United Kingdom - Chan, Wai Meng (Journal of Malaysian and Comparative Law, 2019)
This article proposes to outline the development of the doctrine of privity and provide some examples of the injustice and inconvenience caused by it. The provisions and effects of the 1999 Act will also be studied.